PENGARUH ELECTRONIC WORD OF MOUTH DAN ELECTRONIC SERVICE QUALITY PADA AKUN INSTAGRAM @EXPLORESEMARANG TERHADAP KEPUTUSAN BERKUNJUNG MELALUI MINAT BERKUNJUNG SEBAGAI VARIABEL MEDIASI (STUDI PADA PENGUNJUNG TEMPAT WISATA LAWANG SEWU, SAM POO KONG DAN MASJID AGUNG JAWA TENGAH) - Ayu Virtarini; Ngatno Ngatno (Jurnal Ilmu Administrasi Bisnis, 2020)
Information and communication technology in the world especially the internet is experiencing quite rapid development. The internet provides many conveniences in communicating with many people in a short time. The existence of this phenomenon that many use to promote tourism. This research model examines the effect of electronic word of mouth and electronic service quality on the Instagram @exploresemarang account on the decision to visit through interest in visiting as a mediating variable. The population in this study as many as 100 respondents using purposive sampling and accidental sampling techniques, which means the sampling technique according to certain criteria. The measurement scale uses a Likert scale. Data analysis used regression test, correlation test, determination test, significance test, and single test with SPSS version 25. Based on the results of the study note that all hypotheses have a significant effect with p value <0.05. This means that the better electronic word of mouth and electronic service quality on the Instagram account @exploresemarang will form a visiting interest so as to convince consumers to decide to visit.